Strategi Social Media Marketing untuk Meningkatkan Brand Awareness melalui Instagram pada Usaha Hidroponik Jatinangor Urban Farming - Rahmawati, Desy; Mukti, Gema Wibawa (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Jatinangor Urban Farming (JUF) faces challenges in enhancing brand awareness despite utilizing Instagram as a marketing platform. This study aims to analyze the implementation of social media marketing strategies in increasing brand awareness for Jatinangor Urban Farming through Instagram and to formulate strategies for optimization. The research employs a qualitative approach with SWOT analysis to evaluate internal and external factors influencing digital marketing strategies. The findings indicate that Jatinangor Urban Farming has implemented social media marketing based on the dimensions of online communities, interaction, sharing of content, accessibility, and credibility. However, its execution remains suboptimal. The brand awareness level of Jatinangor Urban Farming is still at the brand recognition stage, necessitating additional strategies to enhance brand recall. The SWOT analysis positions JUF in Quadrant I, signifying strong internal capabilities and significant external opportunities. Therefore, the recommended strategies include strengthening brand identity through educational and interactive content, optimizing data-driven digital marketing strategies to enhance monetization and marketing efficiency, and structuring content management through a content guideline and content calendar. By implementing a more structured strategy, Jatinangor Urban Farming is expected to enhance its brand awareness, visibility and competitiveness in the market.